Imaging stressed organelles via sugar-conjugated color-switchable pH sensors. Issue 4 (16th January 2020) - Zhang, Enkang; Wang, Siyu; Su, Xinhui; Han, Shoufa
Abstract : Sugar-conjugated pH sensors discriminate stressed lysosomes in different cell starvation conditions via red-to-green fluorescence switch. Abstract : Stressed organelles are often challenging to image with canonical organelle probes owing to their propensity to dissipate from stressed organelles. We herein report the imaging of stressed lysosomes with color-switchable glyco-probes that contain an entity of mannose-6-carboxylate or sialic acid for targeting to and long-term retention in stressed lysosomes, and a diad of fluorescein/rhodamine-X-lactam exhibiting dramatic red-to-green fluorescence shift upon pH elevation. Relative to acidotropic dyes prone to dissipate from pH-elevated lysosomes, both glyco-probes are stably trapped in lysosomes without resorting to lysosomal acidity. Importantly, these probes are red emissive in acidic lysosomes (pH 4.5–5.8), but switched to green fluorescence in lysosomes of pH 6.0–7.4, allowing dual color discrimination of lysosomal pH alterations in cell starvation. These results support the use of sugar-armed sensors to investigate stressed lysosomes in biology and disease.